Trichoscapa Karawajewi and its Synonyms (Hymenoptera: Formicidae) - William L. Brown (Psyche: A Journal of Entomology)
A recent loan fom the Zoological Institute, Ukrainian Academy of Sciences, Kiev, Ukrainia, through the kindness of Dr. Alexander G. Radchenko, has allowed me for the first time to examine the type of Strumigenys emeryi Karawajew, which proves to be an example of the same species I later described as Smithistruma dubia. Since S. emeryi was preoccupied in Strumigenys, I had already given it the replacement name Strumigenys (Trichoscapa) karawajewi. The necessary synonymy follows.